Defective jagged-1 signaling affects GnRH development and contributes to congenital hypogonadotropic hypogonadism - Ludovica Cotellessa; Federica Marelli; Paolo Duminuco; Michela Adamo; Georgios E. Papadakis; Lucia Bartoloni; Naoko Sato; Mariarosaria Lang-Muritano; Amineh Troendle; Waljit S. Dhillo; Annamaria Morelli; Giulia Guarnieri; et al. (JCI Insight, 2023)
In vertebrate species, fertility is controlled by gonadotropin-releasing hormone (GnRH) neurons. GnRH cells arise outside the central nervous system, in the developing olfactory pit, and migrate along olfactory/vomeronasal/terminal nerve axons into the forebrain during embryonic development. Congenital hypogonadotropic hypogonadism (CHH) and Kallmann syndrome are rare genetic disorders characterized by infertility, and they are associated with defects in GnRH neuron migration and/or altered GnRH secretion and signaling. Here, we documented the expression of the jagged-1/Notch signaling pathway in GnRH neurons and along the GnRH neuron migratory route both in zebrafish embryos and in human fetuses. Genetic knockdown of the zebrafish ortholog of JAG1 (jag1b) resulted in altered GnRH migration and olfactory axonal projections to the olfactory bulbs. Next-generation sequencing was performed in 467 CHH unrelated probands, leading to the identification of heterozygous rare variants in JAG1. Functional in vitro validation of JAG1 mutants revealed that 7 out of the 9 studied variants exhibited reduced protein levels and altered subcellular localization. Together our data provide compelling evidence that Jag1/Notch signaling plays a prominent role in the development of GnRH neurons, and we propose that JAG1 insufficiency may contribute to the pathogenesis of CHH in humans.